Role of Adolescents’ Reproductive Health Information and Counselling Program towards Knowledge and Attitude in Pregnancy Planning among Adolescent Female in Malang City - Dini Eka Pripuspitasari (Warmadewa University, 2018)
Abstract Each adolescent will experience changes related to reproductive health problems. The growth and sexual maturity drive happens earlier in women rather than in men. KPAI survey data in 2017 states that 97% of adolescents in Indonesia have watched pornographic films and 93.7% have ever done kissing, petting, and oral sex. Malang City Health Office noted in 2014, 139 teenagers aged less than 18 years have been pregnant and increased to 176 cases in 2015. This condition implies that adolescent in Malang city has a big risk of experiencing morbidity and mortality related to the condition of maternal pathology. Following this kind of problem, BKKBN established the Reproductive Health Information and Counselling Program (PIK-KRR) as a platform for young people to prepare for a family life. Through that program, each adolescent female will receive support to understand the substance of pregnancy planning, which includes the physical, psycho-social, and social economy aspects. The main objective is that each adolescent female will postpone the age of marriage and pregnancy before they are able to fulfill those essential aspects. The aim of this research is to understand the role of the Reproductive Health Information and Counselling Program in its relation to the knowledge and the attitude of adolescent females towards pregnancy planning in Malang city. This research applies the comparative observational design by using a proportional sampling technique for 350 students of selected high schools who provide such program and 350 students of selected high schools who do not provide such program. The instrument used for data collection is the questionnaire that has gone through validity and reliability tests. The research data are then analyzed and interpreted by SPSS window release computer program version 23. The results of the knowledge scoring with the category of lack of knowledge in the high school without PIK-KRR group showed the biggest difference compared to that of in the high school group with PIK-KRR. This proves that PIK-KRR contributes meaningfully to the knowledge of high school students. Likewise in the high school groups that have the PIK-KRR, the category of female students with a positive attitude is greater than that of high schools that do not have PIK-KRR. This proves that the presence of PIK-KRR has a significant influence on attitudes in pregnancy planning in adolescents in Malang City. This study shows that there is a significant difference in knowledge and attitude (p=0,00